Pengaruh Sikap Perawat Terhadap Pelayanan Kesehatan pada Rumah Sakit Rehabilitasi Medik dan Paru Peureulak Aceh Timur - Jamilah; M Djamil HS (Jurnal Ekonomi Manajemen dan Sekretari, 2021)
-This study aims to explore the influence of nurses' attitudes towards health services at the Peureulak Medical and Pulmonary Rehabilitation Hospital, East Aceh. The multiple linear regression analysis method was used to measure the relationship between nurses' attitudes (including communication, empathy, professionalism, and concern for patient welfare) and the quality of health services. The results showed that nurses' attitudes significantly influenced patient experience and satisfaction at the hospital. These findings emphasize the importance of developing positive attitudes in nurses as part of a quality management strategy in hospitals. Most respondents expressed a positive perception of nurses' attitudes, indicating high awareness and commitment from nurses to provide the best service to patients. The practical implications of this research are to provide insight for hospital management in designing policies and training programs aimed at improving nurses' attitudes and the overall quality of health services. By paying attention to the positive attitude of nurses, hospitals can create a supportive environment to provide quality services and meet patient expectations